Aptamer‐Conjugated Biocompatible Nanospheres for Fluorescent Imaging–Guided Hepatocellular Carcinoma–Targeted Phototherapeutic Modality. Issue 9 (12th June 2022) - Zhang, Mi; Xiao, Xinyu; Liu, Liang; Liu, Shanshan; Liu, Haichuan; Fan, Taojian; Zhang, Bin; Wageh, Swelm; Al-Ghamdi, Ahmed; Wang, Meijiao; Wang, Jianwei; Du, Chengyou; et al.
Abstract : Conventional strategies against hepatocellular carcinoma (HCC) remain unsatisfactory due to its invasiveness and poor prognosis. Herein, it is utmost imperative to require alternative modalities with less invasiveness, good clinical efficacy, and low side effects. A combination of photothermal therapy (PTT) and photodynamic therapy (PDT) is an emerging modality against refractory HCC. To date a majority of PTT/PDT paradigms has a disappointing therapeutic efficiency, owing to low targeting ability of nanotheranostic agents or imprecise irradiation of lasers. In this study, HCC‐specific targeting aptamer and chlorine e6 (Ce6)‐modified polydopamine (PDA) nanospheres with decoration of Pt quantum dots (termed Apt‐Ce6‐PDA@Pt bioconjugates) are explored to combat HCC in vivo by synergy of PTT and PDT modalities. The Apt‐Ce6‐PDA@Pt bioconjugates can effectively accumulate into tumor sites by specifically binding Glypican‐3 (GPC3)‐positive tumor cells, and core of PDA exerts strong optical absorption in near‐infrared (NIR) region to enable photothermal performance. Meanwhile, the moieties of Ce6 subsequently serve as photosensitizers and fluorophores to generate reactive oxygen species (ROS) and guide phototherapeutics, respectively. The current study finally suggests that Apt‐Ce6‐PDA@Pt bioconjugates can act as a protocol for programmable ablation of HCC and it is believed that it will have a significant impact on clinical translation of promising therapy. Abstract : Herein, hepatocellular carcinoma (HCC)‐specific targeting aptamer and chlorine e6 (Ce6)‐modified strawberry‐like polydopamine (PDA) nanospheres with decoration of Pt quantum dots (termed Apt‐Ce6‐PDA@Pt bioconjugates) are explored to specifically target and combat HCC in vitro and in vivo by synergy of photothermal therapy (PTT) and photodynamic therapy (PDT) modalities. This new type of theranostic agent exerts excellent photothermal and photodynamic performances for long‐term and programmable killing of HCC under light exposure.